The rCC16 Protein Protects Against LPS-Induced Cell Apoptosis and Inflammatory Responses in Human Lung Pneumocytes - Lin, Jinle; Li, Jiemei; Shu, Min; Wu, Weigang; Zhang, Wenwu; Dou, Qingli; Wu, Jian; Zeng, Xiaobin (Frontiers in Pharmacology, 2020)
Objective: Our previous clinical study showed that low lung levels of CC16 strongly influence the occurrence and development of ARDS. The aim of the present study was to evaluate the therapeutic effect of rCC16 on LPS-induced inflammation in A549 cells and to determine its mechanism. Methods: Cell apoptosis and inflammation was induced by LPS stimulation. The cytotoxic effect of rCC16 was evaluated using the MTT assay. Cytokine levels were determined using enzyme-linked immunosorbent assays. The molecular mechanism of rCC16 was investigated by analyzing relevant signaling pathways. Results: The LPS treatment of A549 cells significantly decreased cell viability, increased the levels of the apoptotic proteins Bax, Bak and Cleaved Caspase-3, the secretion of inflammatory cytokines, and the expression levels of TLR4, p-NF/κB, MAPK proteins. While the levels of Bcl-2, p-AKT, p-mTOR, p-ERK1/2, NF/κB, p-AMPK, and p-p38 were significantly decreased in LPS-treated A549 cells. Our experimental results also confirmed that rCC16 inhibited LPS-induced apoptosis, promoted A549 cell proliferation by activating the PI3K/AKT/mTOR/ ERK1/2 pathway, and inhibited the release of certain inflammatory factors, especially HMGB1, through dephosphorylation and inactivation of the TLR4/NF-κB/AMPK signaling pathways. Conclusion: These results highlight the potential utility of CC16 as an important cytokine for the prevention or treatment of inflammation and show that CC16 may play an important role in the future clinical treatment of ARDS.